2011
DOI: 10.1111/j.1551-2916.2011.04517.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Water on Crack Self-Healing in Soda-Lime Silicate Glass

Abstract: The self-healing behavior of radial cracks generated by Vickers indentation in float glass is analyzed when heat treated at 6201C under various atmospheres. Results evidence that two main driving forces influence radial crack evolution: release of residual stresses induced by initial indentation and capillary forces due to surface energy minimization. Depending on the viscosity level, viscous flow allows crack morphological changes driven by capillarity forces or not. Our results evidence that at 6201C, the vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(43 citation statements)
references
References 27 publications
6
37
0
Order By: Relevance
“…Girard et al (2011) reached similar conclusions as those of Hirao and Tomozawa concerning the lowering of viscosity by water and the enhancement of crack healing. Holden and Fréchette (1989) also concluded that a certain degree of moisture is necessary for crack healing in soda-lime-silica glass annealed at 550°C and that a compressive stress assists self-welding of contacting glass plates during annealing, provided that it is not so high that it prevents moisture from reaching the interface, if the stress is applied before the temperature rise.…”
Section: Literature On Thermally-induced Crack Healing In Glasses Arosupporting
confidence: 86%
See 1 more Smart Citation
“…Girard et al (2011) reached similar conclusions as those of Hirao and Tomozawa concerning the lowering of viscosity by water and the enhancement of crack healing. Holden and Fréchette (1989) also concluded that a certain degree of moisture is necessary for crack healing in soda-lime-silica glass annealed at 550°C and that a compressive stress assists self-welding of contacting glass plates during annealing, provided that it is not so high that it prevents moisture from reaching the interface, if the stress is applied before the temperature rise.…”
Section: Literature On Thermally-induced Crack Healing In Glasses Arosupporting
confidence: 86%
“…A polished glass surface is, however, not equivalent to a naturally-formed fracture surface, neither in terms of electrical state -since a fracture surface is charged (Xie et al, 2013) -nor in terms of chemical state -since a fracture surface has got many broken bonds and is thus very chemically active -nor even in terms of roughness or degree of hydration, the latter with a paramount influence on healing, as shown by Girard et al (2011). Moreover, the compression applied during annealing cannot be as uniform on a relatively rough crack face as on polished plate.…”
Section: Thermally-induced and Mechanically Assisted Welding Of Glassmentioning
confidence: 95%
“…The viscosities of glasses and silicate melts decreases with water content, which presents as OH and molecular H 2 O . As the humid atmosphere decreases the viscosity of glass near the crack surface, the crack healing is enhanced in a moist atmosphere . The kinetics of crack healing is studied using radial cracks generated by Vickers indentation, the morphology of which changes with time by heat treatment .…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the concept has been developed in glassy materials, for instance to prevent the leakage of reactant gases through seals in Solid Oxide Fuel Cells . The healing property can be obtained either by the softening of the glass matrix itself or by the oxidation of active particles dispersed into the glassy matrix …”
Section: Introductionmentioning
confidence: 99%